Cross-media Transmission Processes: Marian Figures in TODO SOBRE MI MADRE (Pedro Almodóvar, ES 1999) Journal for Religion, Film and Media - Natalie Fritz (Journal for Religion, Film and Media, 2015)
This paper builds on aspects of the cultural studies perspective that understands art itself as a method of cultural analysis. This will be exemplified by focusing on how film as a cultural technique for framing and reframing the world, using its different audio-visual devices of representation, is an important contemporary agens in the process of transmitting religious motifs and concepts. The paper highlights how Pedro Almodóvar skillfully stimulates the audience to reflect on the polysemy and polyvalence of motifs by not only referring explicitly to iconographic traditions, but also playing with aesthetic conventions.